Lyndon Johnson and the American dream - Goodwin, Doris Kearns (New York : St. Martin's Press, 1976)
Takes us through the vast landscape of Johnson's political and personal life: from his childhood, dominated by an indulgent mother and a hell-raising politico father, through his early political victories and the ideals that inspired them; from the Washington system that trained him, through his election as Vice President and the transitional year, 1964, when JFK's assassination brought him to the highest office in the land; from the remarkable talents that brought him triumph, to the inner demons that tormented him and the flaws that engendered his ultimate tragedy.
Chapter 1. Growing up -- Chapter 2. Education and dream of success -- Chapter 3. The making of a politician -- Chapter 4. Rise to power in the senate -- Chapter 5. The senate leader -- Chapter 6. The vice-presidency -- Chapter 7. The transition year -- Chapter 8. The great society -- Chapter 9. Vietnam -- Chapter 10. Things go wrong.
Includes index.
Keywords: BIOGRAPHIES